1988
DOI: 10.1085/jgp.92.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Purified ryanodine receptor from rabbit skeletal muscle is the calcium-release channel of sarcoplasmic reticulum.

Abstract: The ryanodine receptor of rabbit skeletal muscle sarcoplasmic reticulum was purified as a single 450,000-dalton polypeptide from CHAPS-solubilized triads using immunoaffinity chromatography. The purified receptor had a [aH]ryanodine-binding capacity (Bm~,) of 490 pmol/mg and a binding affinity (Kd) of 7.0 nM. Using planar bilayer recording techniques, we show that the purified receptor forms cationic channels selective for divalent ions. Ryanodine receptor channels were identical to the Ca-release channels des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
320
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(353 citation statements)
references
References 44 publications
(97 reference statements)
32
320
1
Order By: Relevance
“…Ryanodine receptor (RyR)-mediated Ca 2+ release is one of the most important mechanisms in the regulation of cytosolic Ca 2+ concentrations (Berridge, 1993). Ca 2+ -induced Ca 2+ release (CICR), a release mechanism from the sarcoplasmic reticulum (SR) extensively studied in skinned ®bres (Endo, 1977; and in isolated SR vesicles (Meissner, 1984;Meissner et al, 1986;Smith et al, 1986), has been shown to be a function of the RyR (Imagawa et al, 1987;Lai et al, 1988;Hymel et al, 1988;Smith et al, 1988).…”
Section: +mentioning
confidence: 99%
“…Ryanodine receptor (RyR)-mediated Ca 2+ release is one of the most important mechanisms in the regulation of cytosolic Ca 2+ concentrations (Berridge, 1993). Ca 2+ -induced Ca 2+ release (CICR), a release mechanism from the sarcoplasmic reticulum (SR) extensively studied in skinned ®bres (Endo, 1977; and in isolated SR vesicles (Meissner, 1984;Meissner et al, 1986;Smith et al, 1986), has been shown to be a function of the RyR (Imagawa et al, 1987;Lai et al, 1988;Hymel et al, 1988;Smith et al, 1988).…”
Section: +mentioning
confidence: 99%
“…Although the flux through a single SR Ca channel has not been measured inside a frog cut muscle fiber, it has been measured in bilayers that contain either nadve channels (Smith, Coronado, and Meissner, 1986) or channels from purified ryanodine receptor protein (Smith, Imagawa, Ma, Fill, Campbell, and Coronado, 1988) from rabbit skeletal muscle. With 53 mM Ca on the side of the bilayer that corresponds to the lumen of the SR, the single-channel current is ~3 pA at 0 mV, 90-99~ As far as we are aware, currents in single channels from skeletal muscle have not been measured with concentrations of Ca as low as 1-9 mM, the estimated free concentration inside the SR (Hasselbach and Oetliker, 1983).…”
Section: Implications Of the Idea That Only A Small Fraction Of Sr Camentioning
confidence: 99%
“…There is considerable evidence, however, that the single-channel current is not directly proportional to free [Ca] between 1-9 and 53 mM. Smith et al (1988) studied single channels in bilayers with the same concentration of Ca on both sides of the membrane. They found that the relation between conductance at 0 mV and [Ca] could be fitted by a 1:1 binding isotherm with Km --3 mM.…”
Section: Implications Of the Idea That Only A Small Fraction Of Sr Camentioning
confidence: 99%
“…Among these are a 105 000-Da Ca 2+ -transporting ATPase (Brandl et al, 1986(Brandl et al, , 1987; phospholamban, a 27000-29 000-Da pentamer whose phosphorylation is associated with stimulation of Ca 2+ uptake (Kirchberger et al, 1974;Tada et al, 1974); calsequestrin, a 55 000-Da protein that binds Ca 2+ within the sarcoplasmic reticulum with low affinity and high capacity ; two glycoproteins, 53000-Da and 130 000-Da, whose functions remain unknown but which may be involved in intraluminal Ca 2+ -binding and regulation of Ca 2+ uptake ; Campbell and M a c L e n n o n 1 9 8 1 , C a m p b e l l a n d Pepper et al, 1985;Helmke and Howard, 1987;Leberer et al, 1989a;Leberer et al, 1989b;Kutchai and Campbell, 1989); and a 400000-Da ryanodine-sensitive Ca 2+ channel (Lai et al, 1988;Innui et al, 1987;Campbell et al, 1987;Smith et al, 1988). The Ca 2+ -transporting ATPase of cardiac sarcoplasmic reticulum, like phospholamban, is the product of a gene expressed in cardiac and slow-twitch skeletal muscle but not in fast-twitch skeletal muscle (whose sarcoplasmic reticulum Ca 2+ ATPase is the product of a separate gene; Brandl et al, 1986).…”
Section: Discussionmentioning
confidence: 99%